Engineering aphid transmission of foxtail mosaic virus in the presence of potyvirus helper component proteinase through coat protein modifications. (13th April 2023) - Jiang, Jun; Yu, Eric; Nihranz, Chad T.; Prakash, Ved; Varsani, Suresh; Casteel, Clare L.
Abstract : Biotechnologies that use plant viruses as plant enhancement tools have shown great potential to flexibly engineer crop traits, but field applications of these technologies are still limited by efficient dissemination methods. Potyviruses can be rapidly inoculated into plants by aphid vectors due to the presence of the potyviral helper component proteinase (HC-Pro), which binds to the DAG motif of the coat protein (CP) of the virion. Previously it was determined that a naturally occurring DAG motif in the non-aphid-transmissible potexvirus, potato aucuba mosaic virus (PAMV), is functional when a potyviral HC-Pro is provided to aphids in plants. The DAG motif of PAMV was successfully transferred to the CP of another non-aphid-transmissible potexvirus, potato virus X, to convey aphid transmission capabilities in the presence of HC-Pro. Here, we demonstrate that DAG-containing segments of the CP from two different potyviruses (sugarcane mosaic virus and turnip mosaic virus), and from the previously used potexvirus, PAMV, can make the potexvirus, foxtail mosaic virus (FoMV), aphid-transmissible when fused with the FoMV CP. We show that DAG-containing FoMVs are transmissible by aphids that have prior access to HC-Pro through potyvirus-infected plants or ectopic expression of HC-Pro. The transmission efficiency of the DAG-containing FoMVs varied from less than 10 % to over 70 % depending on the length and composition of the surrounding amino acid sequences of the DAG-containing segment, as well as due to the recipient plant species. Finally, we show that the engineered aphid-transmissible FoMV is still functional as a plant enhancement resource, as endogenous host target genes were silenced in FoMV-infected plants after aphid transmission. These results suggest that aphid transmission could be engineered into non-aphid-transmissible plant enhancement viral resources to facilitate their field applications.